Computer Equity for Young Women in Rural Schools - Walter M. Mathews; Linda Wyrick Winkle (Journal of Research in Rural Education, 1982)
The authors define computer equity as equal access to computer literacy for each person. It involves both awareness and action; it implies differing approaches to meet differing needs. Their concern is for the unmet needs of young women - especially those in rural schools. many of whom continue to follow stereotyped role patterns that limit the definition of what a woman can become. While computer literacy is fast becoming a survival skill for a rapidly approaching future. many rural females remain basically unaware of the computer's impact on society and of its impact - both present and potential- on their lives. This article describes persistent external and internal barriers regarding computer literacy that are limiting rural women. It outlines action that rural schools can take to eliminate these factors, thus providing more freedom for rural women to pursue the multiple life options that are beginning to open for their urban counterparts